Easter Bunny on the loose! - Wax, Wendy (Wendy Anne); Garbot, Dave (New York : Harper, 2013)
Looking forward to the annual Easter egg delivery, an Easter Bunny is dismayed to find that his golden egg has been stolen, in a tale that invites readers to locate hidden objects and characters.
Keywords: Easter -- Fiction; Rabbits -- Fiction; Picture puzzles; Easter -- Fiction; Rabbits -- Fiction; Picture puzzles